Rehmannia glutinosa polysaccharide liposome as a novel strategy for stimulating an efficient immune response and their effects on dendritic cells - Huang Y (Dove Medical Press, 2016)
Yee Huang,1 Tao Qin,2 Yifan Huang,2 Zhenguang Liu,1 Ruonan Bo,1 Yuanliang Hu,1 Jiaguo Liu,1 Yi Wu,1 Deyun Wang1,2 1College of Veterinary Medicine, Institute of Traditional Chinese Veterinary Medicine, College of Veterinary Medicine, Nanjing Agricultural University, Nanjing, 2College of Animal Science and Veterinary Medicine, Fujian Agriculture and Forestry University, Fuzhou, People’s Republic of China Abstract: Nanomedicine, the medical application of nanotechnology, promises a seemingly limitless range of applications from drug delivery to adjuvants and therapeutics. Our current research is focused on natural polymer-based liposome adjuvants. With the aim of inducing protective and long-lasting immunity, the immunological adjuvant activity of Rehmannia glutinosa polysaccharide liposome (RGPL) was investigated. In vivo, the splenic lymphocyte proliferation ratios and ovalbumin-specific immunoglobulin G titers of ovalbumin-RGPL-vaccinated mice were significantly upregulated. In draining lymph nodes, the expression of MHC II+CD11c+ and CD86+CD11c+ was increased by RGPL; in addition, the percentages of central memory cells (TCM) and effector memory cells (TEM) were also elevated. RGPL could effectively provide adequate antigen exposure in lymph nodes. In vitro, RGPL could promote dendritic cell maturation and enhance dendritic cell functions, such as the mixed lymphocyte reaction and antigen presentation. Overall, the results demonstrated that RGPL has the potential to act as an effective controlled release vaccine adjuvant. Keywords: Rehmannia glutinosa polysaccharide liposome, adjuvant, controlled release, ovalbumin, dendritic cells